Analysis of the Implementation of the Recycling Program by the Municipality Association Msur, Metropolitan Region, Chile - Mery-Camposano, P; Seal-Mery, C (American Institute of Physics, 2023)
The study analyzed the implementation of the municipal recycling program from the municipality association MSUR. This study considers only the first year of the program that corresponded to the year 2020. The segregated recollection involved a total of 10 municipalities from the Metropolitan Region in Chile. The focus of the program was the recollection paper, glass and PET and the subsequent sale of the materials as recycled to different companies. The analysis was centered in the estimating the weight per municipality recollected, the distribution of the material to be recycled and per capita recycled by each municipality. The first month the program recollected 257.962 kg of material and reached a maximum of 561.827 kg, were it stabilized with an average of 543.840 kg and a standard deviation of 15.600 kg. The percentage of population that the program served depended on the number of vehicles dedicated to each municipality which lead to a variation of the coverage between municipalities that varied between 2,3 to 97,7 percent. The amount of material recovered depended on the municipality and was between 0,016 to 0,124 kg/pp/day. Due to the pandemic, it was observed a small decrease in the amount of recyclable material recollected due to the SARS-CoV-2. As initial result of the program, it was observed that the two municipalities with the highest percentage of coverage area and economical income, were part of municipalities with lowest recovery per capita by weight in the program. This result led to the analysis of the composition of the solid waste for these two municipalities and the inhouse method of segregation. From this part of the analysis, it was possible to observed in the field that the Municipalidad de La Reina had overestimated the percentage of coverage area and the community didńt dispose the recyclables adequately for the segregated recollection. In the case of the Municipalidad de Santiago it was observed that it has a well inhouse structured program, but not all the members of the community are participating, and the spectrum of recyclables is very limited and therefore losing an important fraction of elements that can be recycle. © 2023 Author(s).